2017
DOI: 10.1002/tesq.394
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Strategies and the Reframing of English: Activity Design and Challenges for Teachers in Contexts of Extensive Extramural Encounters

Abstract: Motivational strategies are underresearched, and studies so far conducted have been in sociolinguistic contexts where English is not extensively encountered outside the classroom. Given also that little is known about strategies relating to the design and content of classroom activities, the purpose of this study is to identify and critically evaluate strategies focusing on activity design and content in classroom activities that, in a setting where students have extensive extramural English encounters, teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
5
43
1
Order By: Relevance
“…As the goal was to determine how course materials of the ELC serve to aid students in the development of ICC, a careful scrutiny of course syllabi and of course materials was carried out; ongoing class observations were conducted; the author's own experience as a teacher of the ELC was of course taken into account. In keeping with other findings (see Bao, 2013;Jolly & Bolitho, 2011;Pulverness & Tomlinson, 2013), the analysis concluded that tailor-made materials, some produced within the ELC and some commercially produced for a Chinese audience, best allowed students to be themselves and at the same time simulate "the sorts of communicative activities which are required of them outside" (Nunan, 1988, p. 97; see also Bao, 2013;Henry, Korp, Sundqvist, & Thorsen, 2017). The analysis also concluded that, while various techniques were employed in the ELC to develop learners' ICC, text-driven, task-based techniques appeared to be the most common.…”
Section: Methodssupporting
confidence: 60%
“…As the goal was to determine how course materials of the ELC serve to aid students in the development of ICC, a careful scrutiny of course syllabi and of course materials was carried out; ongoing class observations were conducted; the author's own experience as a teacher of the ELC was of course taken into account. In keeping with other findings (see Bao, 2013;Jolly & Bolitho, 2011;Pulverness & Tomlinson, 2013), the analysis concluded that tailor-made materials, some produced within the ELC and some commercially produced for a Chinese audience, best allowed students to be themselves and at the same time simulate "the sorts of communicative activities which are required of them outside" (Nunan, 1988, p. 97; see also Bao, 2013;Henry, Korp, Sundqvist, & Thorsen, 2017). The analysis also concluded that, while various techniques were employed in the ELC to develop learners' ICC, text-driven, task-based techniques appeared to be the most common.…”
Section: Methodssupporting
confidence: 60%
“…These insights have importance for English language teaching. In situations where students have extensive experiences of English in online environments, teachers’ instructional repertoires increasingly include digital technologies (Henry et al., ). In understanding the emergence of L2 motivation in networked spaces, it is important that influences stemming from digitally mediated social interaction are adequately conceptualized.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger, multiple‐case study carried out in Sweden. In the Nordic countries, students have extensive encounters with English outside the classroom, and a major motivational challenge facing teachers is to create learning opportunities that connect with these out‐of‐school experiences (Henry, Korp, Sundqvist, & Thorsen, ). In the Motivational Teaching in Swedish Secondary English (MoTiSSE) project, ethnographic research was carried out in the classrooms of 16 English teachers identified as knowledgeable about and interested in students’ out‐of‐school activities involving English, as having a professional practice informed by these insights, and as having students who were generally motivated.…”
Section: Methodsmentioning
confidence: 99%
“…connecting what has to be learned to the students' everyday lives) were used significantly more frequently than the other strategies [1], whereas group work and promoting cooperation only ranked in the middle. Likewise, Henry, Korp, Sundqvist, and Thorsen's research shows that Swedish class showed a high frequency of competition and cultural related motivational strategies [7].…”
Section: A Descriptive Statistical Analysis Of the Motivational Stramentioning
confidence: 96%